1991
DOI: 10.2166/wst.1991.0538
|View full text |Cite
|
Sign up to set email alerts
|

The Selector Effect on Filamentous Bulking in Long Sludge Age Activated Sludge Systems

Abstract: A survey of long sludge age activated sludge plants in South Africa showed that bulking was widespread in nitrogen and nitrogen and phosphorus removal plants with the dominant causative filamentous organisms being the low F/M types 0092, 0675, 0041, Microthrix parvicella, 0914 and 1851. The literature suggests that in aerobic systems proliferation of the low F/M filaments can be controlled by aerobic selector reactors. From an extensive investigation into the selector reactors, and the effect these stimulate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 0 publications
1
16
0
2
Order By: Relevance
“…In the current alternating system, only the presence of microaerophilic conditions in the anoxic stage led to the deterioration of sludge settleability. Many reports can be found in the literature connecting biological nutrient removal (e.g., unaerated sludge mass fraction and frequency of alteration between unaerated and aerobic conditions) to bulking sludge problems (Blackbeard et al, 1988;Eikelboom et al, 1998;Ekama et al, 1996a;Gabb et al, 1991Gabb et al, , 1996Kunst and Reins, 1994;Krhutková et al, 2002;Kristensen et al, 1994;Lakay et al, 1999). Our results clearly indicate that intrinsic BNR conditions of alternating phases do not necessarily lead to bulking sludge, but instead to very sufficiently settled sludge.…”
Section: Relationship Between Feeding Pattern Substrate Gradients Amentioning
confidence: 99%
See 2 more Smart Citations
“…In the current alternating system, only the presence of microaerophilic conditions in the anoxic stage led to the deterioration of sludge settleability. Many reports can be found in the literature connecting biological nutrient removal (e.g., unaerated sludge mass fraction and frequency of alteration between unaerated and aerobic conditions) to bulking sludge problems (Blackbeard et al, 1988;Eikelboom et al, 1998;Ekama et al, 1996a;Gabb et al, 1991Gabb et al, , 1996Kunst and Reins, 1994;Krhutková et al, 2002;Kristensen et al, 1994;Lakay et al, 1999). Our results clearly indicate that intrinsic BNR conditions of alternating phases do not necessarily lead to bulking sludge, but instead to very sufficiently settled sludge.…”
Section: Relationship Between Feeding Pattern Substrate Gradients Amentioning
confidence: 99%
“…After retrofit of the plants to achieve biological nutrient removal (BNR), regular bulking sludge phenomena have occurred in these plants. It is quite commonly reported that BNR process conditions, in which environmental conditions are continuously alternating between aerobic, anoxic, and anaerobic, favor some filamentous microorganisms, mainly the morphotypes Microthrix parvicella, and Types 0092, 0041, and 0675, in competition with floc-forming organisms (Eikelboom, 1994;Eikelboom et al, 1994Eikelboom et al, , 1998Gabb et al, 1991Gabb et al, , 1996Lakay et al, 1999;Krhutková et al, 2002). These bulking phenomena were subsequently directly attributed to the introduction of BNR processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para hacer uso de esta información, se identifican organismos "modelo" que formen parte del surrogado, y las características microbiológicas y bioquímicas conocidas se utilizan para obtener un mejor entendimiento del surrogado. Estudios recientes han encontrado que el enfoque del organismo surrogado es inadecuado en la descripción de algunos patrones de comportamiento observados en sistemas de lodos activados; por ejemplo, en el uso de selectores (Gabb et al, 1991), en el estudio de la inhibición del uso de substratos en transferencias de zonas anóxicas a zonas aerobias (Casey et al, 1994), y en los estudios de generación de productos intermedios del proceso de desnitrificación (Casey et al, 1994). Para poder describir estas y otras observaciones similares, es necesario seleccionar un nivel de organización más fundamental: se requiere modelar la actividad y la síntesis de cierto tipo de enzimas que son claves en los procesos en que participan (Wild et al, 1994).…”
Section: ¿Qué Es Un Modelo?unclassified
“…The anaerobic selector technology was initially developed to improve sludge settling characteristics by inhibiting the growth of filamentous bacteria and facilitating the growth of phosphorus accumulating organisms (PAOs), which store polyphosphate and polyhydroxybutyrate (PHB) doi: 10.2166/wst.2009.025 (Gabb et al 1991). It was reported that, compared to the conventional activated sludge process, savings in aeration energy of up to 30% might be achieved through anaerobic stabilization (ANS) as a result of COD uptake in an anaerobic environment (Wable & Randall 1994;Reusser 2005).…”
Section: Introductionmentioning
confidence: 99%